TRANSFORM AND REBUILD GAMES: AN ANALYSIS USING THE FUNDAMENTAL CATEGORIES PREVALENT IN RECREATIONAL ACTIVITIES CONCEIVED BY CAILLOIS. (Fiep Bulletin - online, 2012)
Since it is a culturally human, man invents and reinvents games and have fun with them since they are aware of its existence. The aim of this study is to analyze the process of transformation and recreation of the game that can occur within the context of the school physical education classes, and see if after the process of rebirth and transformation, the characteristics of this game are changed? The subjects consisted of students from the 1st year of high school EE. Joaquim Abarca. To analyze the game, the process of transformation and recreation was developed three learning situations to be worked with the students. The analysis of the game changed and recreated by students, is conducted through the main categories prevalent in recreational activities which are conceptualized by Caillois (1990): agon (games competition), alea (games of chance), mimicry (simulation games) and ilinx (games of vertigo), and five criteria (one-game as a means to an end and 2 - cooperative values, 3 - valuing creativity; 4 - Inclusion and respect the differences) to be respected by the teachers of Physical Education working games in schools. (DOLIO, 2011). Of all the games developed and experienced by students did an analysis of the game features "fire smart" transformed and recreated by the students. The burning is characterized traditional features in a game with "agony," after its re-creation "Smart Burn" feature "agon" gives way to another feature the "Alea" game of luck. After the analysis, we conclude that the process of transformation and recreation of the game that occurs within the context of school physical education classes, can bring great benefits to the participants. As we can see the initial characteristics of the transformed and re-created games are changed, both in process and final product.
Keywords: Game; Manufacturing; Recreation